Mechanical and rheological properties of steel fibre reinforced self - compacting concrete - Niş, Anıl. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
Main objective of the research was to further understand the diﬀerent parameters aﬀecting performance of SFR-SCC with diﬀerent steel ﬁber volumes and types. Fresh and hardened state properties of these materials were investigated by using several experimental methods. For this purpose 5 mixes; plain and reinforced with 2 diﬀerent ﬁber volumes (0.5 and 1.0%) and two diﬀerent ﬁber lengths; were produced. Flowa bility and rheology as well as static and dynamic segregation resistance of the above mentioned mixes were studied in the fresh state. Specimens with varying sizes were produced with these 5 mixes. Six diﬀerent width and depth (30 mm to 100 mm), four diﬀerent length (200 mm to 425 mm) were used to investigate the eﬀect of shear span to depth ratio (a/d) and specimen thickness to ﬁber length (t/fL) on the mechanical per formance of small size beams. As a result 35 diﬀerent specimen groups were obtained. Compressive strength, splitting tensile strength and 4-point bending tests were carried out on these specimens for thoroughly evaluating mechanical performance and cracking mechanisms. Detailed ﬁber orientation tests were carried out on the selected specimens in the hardened state, to understand the ﬁber orientation states of the specimens and their eﬀects on the resulting performance. The results showed that ﬁber orientation in the casting direction can be made possible by using a casting ﬂow methodology. Both of the investigated parameters (a/d and t/fL ratios) and varying ﬁber parameters were found to highly aﬀect resulting mechanical performance and cracking patterns under bending. 3 point bending tests on notched specimens were done for modeling bending behavior by using an existing model and the model was further developed by introducing new parameters for short FRC.
Keywords: Reinforced concrete construction.; Fibers -- Materials.